A tyrosine-based nanosensor for rapid sensitive detection of copper (II) ions - Lian, Jiaqi; Miao, Pandeng; Na, Na; Khan, Abdul Jamil; Xiang, Ji; Feng, Zhang (Penerbit Universiti Kebangsaan Malaysia, 2020)
Most of the chromophores of fluorescent peptides contain aromatic amino acids with conjugated double bonds, among which tyrosine (Y) has become the focus of researches due to its unique physicochemical (optical, redox, and metal chelation) properties. However, there are few studies on the self-assembly and polymerisation of single. This study shows that the phenol group of Y can be oxidized into benzoquinone group in alkaline conditions and then undergoes polymerisation and further self-assembles into nanoparticles (NPs). The product of pYoxNPs have a strong fluorescence emission peak at 463 nm, and Cu2+ can spontaneously bind to it and dramatically quench their fluorescence. Based on these findings, we developed a rapid, sensitive and specific nanosensor for detecting Cu2+. When the concentration of Cu2+ is within the range of 40 μM - 1 mM, we can obtain a good linear correlation between the fluorescence intensity of pYoxNPs and the concentration of copper ions, and the limit of detection (LOD) is determined to 37.26 μM. In comparison to other modern methods for sensing Cu2+, this method has advantages of simplicity of material synthesis, low cost, robust and rapid in sensing reaction, so we envision a good prospect for Cu2+ detection applications in both bulk and harsh environments.